2004
DOI: 10.1095/biolreprod.104.030056
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Growth Hormone Binding Sites in Granulosa and Theca Layers at Different Stages of Follicular Maturation and Ovulatory Cycle in the Domestic Hen

Abstract: The currently available evidence points to a possible influence of growth hormone (GH) on avian folliculogenesis, which can be mediated by both hepatic- and ovarian-derived IGF-I. Therefore, the purpose of the present study was to reveal GH-binding sites in granulosa and theca layers of preovulatory follicles and to determine the binding characteristics depending on the degree of follicular maturation and the stage of the ovulatory cycle in the hen. Hens were killed 2 h (stage I), 9 h (stage II), 16 h (stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The GHR mRNA and the corresponding immunoreactivity were comparable to GH detected in the stroma of developing ovary and in the wall of all follicles and were more intense in granulosa cells than in theca interna or theca externa. In the sexually mature hen ovary, GH-binding sites have also been shown, by radioreceptor assay, in the granulosa and theca layers of the 5 largest preovulatory follicles, in which the number of GH-binding sites falls in the theca while increasing in the granulosa during follicle enlargement (Lebedeva et al, 2004). A more recent study also revealed presence of GHR protein and GH in cultured granulosa cells which may indicate that the GHR may be activated by systemic or by GH produced locally (Ahumada-Solórzano et al, 2012).…”
Section: Expression and Localization Of Growth Hormone Receptors In Tmentioning
confidence: 98%
“…The GHR mRNA and the corresponding immunoreactivity were comparable to GH detected in the stroma of developing ovary and in the wall of all follicles and were more intense in granulosa cells than in theca interna or theca externa. In the sexually mature hen ovary, GH-binding sites have also been shown, by radioreceptor assay, in the granulosa and theca layers of the 5 largest preovulatory follicles, in which the number of GH-binding sites falls in the theca while increasing in the granulosa during follicle enlargement (Lebedeva et al, 2004). A more recent study also revealed presence of GHR protein and GH in cultured granulosa cells which may indicate that the GHR may be activated by systemic or by GH produced locally (Ahumada-Solórzano et al, 2012).…”
Section: Expression and Localization Of Growth Hormone Receptors In Tmentioning
confidence: 98%
“…The increase in plasma GH concentration in chickens at the time of maturation (Williams et al 1986) and before oviposition ) and the suppression of GH secretion in chicken, turkey and bantam hens during the cessation of egg laying Sharp et al 1979;Bedrak et al 1981) suggest that, in birds, GH might participate in reproduction, as it does in mammals. GH receptors in the granulosa and theca layers of preovulatory follicles (Lebedeva et al 2004) and GH receptor (GHR) mRNA in the ovaries of growing broiler breeder chickens (Heck et al 2003) have also been reported. Although our recent study (Hrabia et al 2008) has shown mRNA expression and protein localization of GH and GHR in each compartment of the hen ovary prior to and after the onset of laying, thereby suggesting a local role of GH in ovarian function, the role of GH in the chicken ovary is unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Control of its activity is multihormonal and includes gonadotrophins and locally produced regulators. One suggested ovarian function regulator is growth hormone (GH; Heck et al 2003;Lebedeva et al 2004;Hrabia et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with those of Heck et al (2003) who have reported the presence of GHR mRNA in the non-compartmentalized ovaries of broiler chickens between 4 and 16 weeks of age. Lebedeva et al (2004) have similarly detected GH-binding sites in the chicken ovary by radioreceptor assay. They have found that the number of GH-binding sites falls in the theca during follicular enlargement, whereas these sites increase in the granulosa.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, in our in vivo and in vitro studies, we have observed an involvement of GH in ovarian steroidogenesis (Hrabia et al 2001;Hrabia and Rząsa 2007). Additionally, use of a radioreceptor assay has revealed GH-binding sites in the granulosa and theca layers of preovulatory follicles (Lebedeva et al 2004). The expression of the GHR gene in the ovaries of broiler breeder hens has also been shown from 4-16 weeks of age by using reverse transcription/polymerase chain reaction (RT-PCR; Heck et al 2003).…”
Section: Introductionmentioning
confidence: 86%